Recent laser upgrades at Sandia's Z-backlighter facility in order to accommodate new requirements for magnetized liner inertial fusion on the Z-machine. (21st October 2016) - Schwarz, Jens; Rambo, Patrick; Armstrong, Darrell; Schollmeier, Marius; Smith, Ian; Shores, Jonathan; Geissel, Matthias; Kimmel, Mark; Porter, John
Abstract : The Z-backlighter laser facility primarily consists of two high energy, high-power laser systems. Z-Beamlet laser (ZBL) (Rambo et al., Appl. Opt.44, 2421 (2005)) is a multi-kJ-class, nanosecond laser operating at 1054 nm which is frequency doubled to 527 nm in order to provide x-ray backlighting of high energy density events on the Z-machine. Z-Petawatt (ZPW) (Schwarz et al., J. Phys.: Conf. Ser.112, 032020 (2008)) is a petawatt-class system operating at 1054 nm delivering up to 500 J in 500 fs for backlighting and various short-pulse laser experiments (see also Figure 10 for a facility overview). With the development of the magnetized liner inertial fusion (MagLIF) concept on the Z-machine, the primary backlighting missions of ZBL and ZPW have been adjusted accordingly. As a result, we have focused our recent efforts on increasing the output energy of ZBL from 2 to 4 kJ at 527 nm by modifying the fiber front end to now include extra bandwidth (for stimulated Brillouin scattering suppression). The MagLIF concept requires a well-defined/behaved beam for interaction with the pressurized fuel. Hence we have made great efforts to implement an adaptive optics system on ZBL and have explored the use of phase plates. We are also exploring concepts to use ZPW as a backlighter for ZBL driven MagLIF experiments. Alternatively, ZPW could be used as an additional fusion fuel pre-heater or as a temporally flexible high energy pre-pulse. All of these concepts require the ability to operate the ZPW in a nanosecond long-pulse mode, in which the beam can co-propagate with ZBL. Some of the proposed modifications are complete and most of them are well on their way.